Challenges in Cell-Based Therapies for the Treatment of Hearing Loss. Issue 11 (November 2018) - Takeda, Hiroki; Dondzillo, Anna; Randall, Jessica A.; Gubbels, Samuel P.
Abstract : Hearing loss in mammals is an irreversible process caused by degeneration of the hair cells of the inner ear. Current therapies for hearing loss include hearing aids and cochlear implants that provide substantial benefits to most patients, but also have several shortcomings. There is great interest in the development of regenerative therapies to treat deafness in the future. Cell-based therapies, based either on adult, multipotent stem, or other types of pluripotent cells, offer promise for generating differentiated cell types to replace lost or damaged hair cells of the inner ear. In this review, we focus on the methods proposed and avenues for research that seem the most promising for stem cell-based auditory sensory cell regeneration, from work collected over the past 15 years. Highlights: Mouse and human pluripotent stem cells can be differentiated into an inner ear supporting cell and functional hair cell fate in vitro as well as into inner ear organoids. Progenitor cells capable of differentiation into inner ear hair cells have been identified in the neonatal and early adult cochlea. Transplantation of pluripotent stem cell-derived progenitors into the chick auditory sensory epithelium as well as the adult rodent auditory nerve leads to survival and terminal differentiation of grafted cells. Transplantation of pluripotent stem cell-derived progenitors into the normal and lesioned rodent cochlea leads to survival, but not integration or terminal differentiation, of grafted cells.